REPRODUCIBILITY AND COMPARISON OF VISUAL ACUITY OBTAINED WITH SIGHTBOOK MOBILE APPLICATION TO NEAR CARD AND SNELLEN CHART. Issue 5 (May 2016) - Phung, Lam; Gregori, Ninel Z.; Ortiz, Angelica; Shi, Wei; Schiffman, Joyce C.
Abstract : Purpose: To investigate test–retest reproducibility of visual acuities obtained with a popular mobile application (app) and to explore the agreement with the standard clinic charts. Methods: Records of patients who had visual acuity measured during the same routine clinic visit with Snellen chart, Rosenbaum near vision card, and SightBook mobile app were reviewed. Acuities were converted to approximate ETDRS letters for statistical purposes. Results: One hundred and twenty-six patients were identified. SightBook, Snellen, and near card acuities had excellent test–retest reproducibility. SightBook acuities were significantly different from the near card acuities (mean absolute difference of 5.4 and 6.1 letters in the right and left eyes) and the Snellen acuities (mean absolute difference of 7.7 and 7.9 letters in the right and left eyes). The agreement was also poor between the near card and the Snellen acuities (mean absolute difference of 6.4 and 7.6 letters in the right and left eyes). Conclusion: The discrepancy between SightBook mobile app and the clinic charts acuities may be large; however, the results are highly reproducible. Obtaining baseline SightBook acuity allows future vision comparisons. SightBook mobile app offers a new portable vision assessment tool for the office and remote patient monitoring. Abstract : SightBook mobile app yields reproducible visual acuity results that may vary significantly from the near card and the Snellen acuities, and thus should not be directly compared. SightBook app offers a new portable vision assessment tool for measuring visual acuity in ophthalmologic offices and for remote patient monitoring.